EFFECTIVENESS OF ECO ENZYME HAND SANITIZER ON DECREASING THE NUMBER OF GERMS ON HANDS WITH DOSAGE SCALE OF 1 : 600 - Rusdi, Rusdi; Daramusseng, Andi; Ridwan, M. Rahul (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2024)
The environmental problem we see today is waste. Around 70% of the total waste generation is dominated by organic waste which is considered only as residual waste that has no economic value. With the high problem of organic waste, one solution to reduce household waste such as fruit and vegetable waste into eco-enzyme is made hand sanitizer. The purpose of this study was to see the effectiveness of eco-enzyme hand sanitizer on reducing the number of germs on hands with a dose scale of 1:600. The type of research used is experimental. The analysis used is univariate and bivariate analysis. The samples in this study were 15 students of the undergraduate of Environmental Health study program, Muhammadiyah University, East Kalimantan. The sampling technique in this research is random sampling. Based on the results of this study, there were 13 students who experienced a decrease in the number of germs on their hands while 2 students experienced an increase in the number of germs on their hands by being treated and after being treated (Hand sanitizer). The results of the Wilcoxon bivariate test between before being treated and after being treated with the use of eco-enzyme hand sanitizers got P 0.001 (smaller than 0.05), then the eco-enzyme hand sanitizer that has been made is effective in killing germs on hands.